Tuning the electronic environment of the anion by using binary ionic liquid mixtures - Men, Shuang; Licence, Peter (Elsevier, 2017)
The electronic environment of the anion is tuned by using binary ionic liquid mixtures employing a com- mon anion and two cations with large difference in acidity. X-ray photoelectron spectroscopy is used to monitor the change of the electronic environment of the anion by measuring the binding energy of elements present in the anion. It is found that due to the large difference in acidity of the two cations, noticeable shifts can be observed for all anion-based components, no matter how basic the anion is.